Adaptive filtering : implementation of algorithms on embedded processor - Lim, Keegan Tien Choon. (2010)
In order to improve the sound quality in telephone communications conference room, researchers explore ways to perform filtering to remove acoustic echo. They are generated due to poor isolation of earpiece and microphone, or in an acoustically reflective environment.